Cover Feature: Durable Flexible Supercapacitors Utilizing the Multifunctional Role of Ionic Liquids (Energy Technol. 1/2018). Issue 1 (1st September 2017) - Lorenzo, Marta; Srinivasan, Geetha
Abstract : Durable Flexible Supercapacitors : The cover image shows the design of durable flexible supercapacitors to power‐up future electronics using an ionic‐liquid technology. The need for durable energy devices is crucial to mankind starting from usage in portable electronics in our daily life such as laptops, smart phones, and tablets, to supplying power for health monitoring and treatment purposes. Currently used lithium‐ion batteries, although possessing long cycle lives, carry hazards associated with harmful organic solvents, electrolyte leakage, potential explosion, high internal resistance, and the challenge to design the device to be flexible. Replacement of lithium‐ion batteries with flexible supercapacitors composed of biocompatible organic composites and safe electrolytes would, therefore, be highly advantageous for biomedical applications such as in medical implants. The flexible conducting polymer–biopolymer composite‐based devices developed by Marta Lorenzo and Dr Geetha Srinivasan at Queen's University Ionic Liquid Laboratories, Belfast, by exploiting the multifunctional role of ionic liquids resulted in ultrathin flexible supercapacitors with excellent cycle lives of over 15000 cycles with nearly 100 % efficiency and a specific capacitance of roughly 5 mF g −1, which is sufficient to activate biosensors. This technology will allow fabrication of task‐specific supercapacitors. More details can be found in the Full Paper by Marta Lorenzo et al. onpage 196 in Issue 1, 2018 (10.1002/ente.201700407 ). The authors thank Mr. Daniel Carreira Rivas for the cover art.